Mid-Atlantic Islands Invertebrate Specialist Group, Newsletter n.º 7 - Wilkins, Vicky (2022)
In this issue, Luís Crespo presents the recent taxonomic revision of the Hognas from Madeira archipelago. Mário Boieiro and Paulo Borges share the new findings of introduced species in the Azores. At the same time, António Franquinho Aguiar brings the new paper of J. Claessens et al. regarding the pollination strategy of the Gennaria diphylla on the Canary and Madeira Islands. Carla Rego et al. talk about the hoverflies from the Madeira archipelago, while Yeray Monasterio informs about the butterflies observation workshops which will take place at La Palma Island (Canaries Islands). Dinarte Teixeira, Marco Neiber and Klaus Groh signal the start of a conservation project in Tenerife addressing five Critically Endangered endemic land snails.